2009
DOI: 10.1303/aez.2009.29
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition preference of two hoverfly species in response to risk of intraguild predation

Abstract: Two experiments were performed in the laboratory to understand the relationships between oviposition preference and larval performance of the two predatory hoverfly species, Episyrphus balteatus de Geer and Metasyrphus corollae Fabricius. We first conducted laboratory experiments to understand the nature and relative strengths of intraguild predation between the larvae of three ladybird species, Harmonia axyridis Pallas, Propylea japonica Thunberg, and Scymnus posticalis Sicard, and two predatory hoverfly spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 37 publications
1
15
1
Order By: Relevance
“…This response is likely to be adaptive as laboratory studies have demonstrated that H. axyridis larvae will eat E. balteatus eggs (Alhmedi et al, unpubl. data) and syrphid larvae (Putra et al, 2009).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This response is likely to be adaptive as laboratory studies have demonstrated that H. axyridis larvae will eat E. balteatus eggs (Alhmedi et al, unpubl. data) and syrphid larvae (Putra et al, 2009).…”
Section: Discussionmentioning
confidence: 89%
“…Most of these studies have focused on coccinellids and chrysopids, while studies on syrphids are very recent and scarce (e.g. Scholz & Poehling, 2000;Pineda et al, 2007;Almohamad et al, 2008;Putra et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known on the intraguild interactions between E. balteatus and H. axyridis. Putra et al (2009) and Alhmedi et al (2010) observed IGP by larvae of H. axyridis on those of E. balteatus, but the former study only used first and last instars of both predators, whereas the latter only performed experiments in the presence of extraguild prey.…”
Section: Introductionmentioning
confidence: 99%
“…For example, do geckos respond to visual cues provided by sleeping skinks or eggs, or do chemosensory cues provided by feces, nests, or the lizards themselves provide enough information to warrant predator avoidance? Some invertebrates avoid nesting in areas containing predator chemosensory cues (e.g., Walzer et al 2006;Turner et al 2007;Putra et al 2009;Choh et al 2010), and geckos can use both visual and chemosensory cues to avoid predators (e.g., Webb et al 2009). These cues will be more common (and thus easier to detect) in areas with high lizard abundance (such as in the artificial wall), which could give the prey more opportunity to avoid predation.…”
Section: Discussionmentioning
confidence: 99%